Spray drift characteristics test of unmanned aerial vehicle spray unit under wind tunnel conditions - Wang, Changling; Zeng, Aijun; He, Xiongkui; Song, Jianli; Andreas, Herbst; Gao, Wanlin (International Journal of Agricultural and Biological Engineering, 2020)
Since the 2010s, unmanned aerial vehicle (UAV) sprayer was applied more and more widely for low-volume aerial pesticides spraying operations in China. However, droplets from the UAV sprayer have a higher drift risk due to more fine droplets sprayed and a higher flight height than ground sprayers. Study on UAV spray drift has been a new hot spot within the field of pesticide application technology. Most of previous studies used direct field methods for spray drift, but the meteorological conditions in field were unstable and uncontrollable, and drift research under an actual operation state in wind tunnel has not been reported. Therefore, 25 treatments of wind tunnel measurements and droplets spectrum tests of 10 models of nozzles were conducted to explore the influence factor on spray drift characteristics of UAV chemicals application in this study. A spray unit with a rotor of UAV was innovatively installed in wind tunnel, and the airstream from the wind tunnel was regarded as the relative moving natural wind to simulate the flight status. The airborne and the sediment spray drift was measured to study the effects of the nozzle type and size (flat fan, hollow cone and air-inclusion nozzles), flight speed, adjuvant (DRS-60, Y-20079, MF and G-611) and meteorological parameters (20°C & 40%, 20°C & 80%, 30°C & 40% and 30°C & 60%). The drift potential (DP) and the drift potential reduction percentage (DPRP) in vertical and horizontal directions were obtained for each test. Both nozzle type and size had an impact on the spray drift potential obviously by affecting the droplet size and the ratio of fine droplets, and the regression linear models between DPRPV/DPRPH and DV50, V75 were established (R2=0.934/0.925). Flight speed also had a significant effect on the spray drift characteristics, and reducing the flight speed could increase the DP effectively. Adding spray adjuvants could affect the DP under experimental meteorological parameters, and the anti-drift performance ranked in the order of DRS-60>MF>Y-20079>G-611. Recommendations were proposed in order to reduce the spray drift for UAV sprayer’s operation. These findings can contribute to provide guidelines and technical support for the wind tunnel spray drift tests of UAV and the field operation regulation of unmanned aerial PPP application. Keywords: unmanned aerial vehicle (UAV) sprayer, wind tunnel, spray drift potential, nozzle, adjuvant DOI: 10.25165/j.ijabe.20201303.5716 Citation: Wang C L, Zeng A J, He X K, Song J L, Herbst A, et al. Spray drift characteristics test of unmanned aerial vehicle spray unit under wind tunnel conditions. Int J Agric & Biol Eng, 2020; 13(3): 13–21.